Jesaja en de biodiversiteitscrisis Bijbellezen in ecologisch perspectief - Dekker, J. 1966- (2025)
Ecological hermeneutics stands for bringing an ecological perspective to biblical interpretation. This article compares the ecocritical reading advocated by the book Hemels groen with three common approaches in ecological hermeneutics. It then focuses on the issue of the enormous biodiversity loss caused by human beings. Based on a discussion of the seraphs' exclamation in Isaiah 6:3b and the praise of the wild animals in Isaiah 43:20, it is argued that biodiversity loss has a profound theological and spiritual impact. Humanity directly harms God's glory and deprives Him of a significant part of the praise due to Him. Despite its theocentric focus, Reformed theology has not sufficiently resisted this. As a result, creation has not been given adequate attention in Reformed religious practice and belief. Acknowledging and appreciating the place of creation in the theology of Isaiah helps to listen better to the language spoken by non-human creation today.